Negotiating with the Russians - edited by Raymond Dennett and Joseph E. Johnson. (World Peace Foundation, 1951)
Negotiating on military assistance, 1943-1945, by J. R. Deane.--Negotiating under lend-lease, 1942-1945, by J. N. Hazard.--Negotiating the Nuremberg trial agreements, 1945, by S. S. Alderman.--Negotiating at Bretton Woods, 1944, by R. F. Mikesell.--Negotiating to establish the Far Eastern Commission, 1945, by G. H. Blakeslee.--Negotiating on refugees and displaced persons, 1946, by E. F. Penrose.--Negotiating on the Balkans, 1945-1947, by M. Ethridge and C. E. Black.--Negotiating on atomic energy, 1946-1947, by F. Osborn.--Negotiating on cultural exchange, 1947, by E. J. Simmons.--Some Soviet techniques of negotiation, by P. E. Mosely.